Knowledge, Attitudes, and HIV/AIDS Risk Behaviors of Myanmar Migrant Workers in Thailand - Nitchamon Rakkapao; Pradabduang Kiattisaksiri; Ronnapoom Samakkekarom (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: HIV/AIDS is still a problem in the health care system of developing countries. Migrant workers are considered a vulnerable population for HIV infection. The current information on HIV/AIDS and migrant workers is useful to provide suitable effective health interventions for the prevention of HIV/AIDS. This study aims to describe knowledge, attitudes and HIV/AIDS risk behaviors among Myanmar male migrant workers in Thailand. Methods: A cross-sectional study was conducted in Myanmar male migrant workers aged 18-60 years collected from February to May 2018. A total of 400 migrant workers who live in Patumthani provinces were selected by a convenience sampling method. Descriptive statistics were used to explore knowledge, aô€¦®tudes and HIV/AIDS risk behaviors of participants. Results: The mean age of the participants was 33 years, ages ranged from 18 to 60 years old, achieved primary school (40.40%), and married (54.30%). An average living in Thailand was 3.25 years and monthly income was 9,166 baht (_286 USD), respectively. A majority of participants had a poor level of HIV/AIDS knowledge (55.25%) and a fair level of an attitude about HIV/AIDS disease and prevention (61.25%). Risk behaviors related to HIV/AIDS of participants who had sex with non-partners were 40.58%. Conclusion: Most participants had poor knowledge and a fair attitude of HIV/AIDS. Risk behaviors related to HIV/AIDS of the participants were relatively high. Moreover, most of participants had less access to health care services. This results confirmed that an urgent need to provide health intervention to increase knowledge on HIV/AIDS of Myanmar migrant workers in Thailand. Keywords: Myanmar migrant workers, HIV/AIDS, risk behavior, Thailand Received: 19 May 2019 Reviewed: 8 June 2019 Revised: 24 June 2019 Accepted: 1 July 2019 DOI: 10.35898/ghmj-33581